Emerging Infections in Asia - Lu, Yichen; Essex, Max; Roberts, Bryan (Springer US : Imprint: Springer, 2008)
Emerging Infections in Asia Edited by Yichen Lu, Harvard School of Public Health, Boston M. Essex, Harvard School of Public Health, Boston Bryan Roberts, Apex Consulting Group, Cambridge, Massachusetts Ongoing population shifts, widening health disparities, and rapid genetic mutations are major factors in viral and bacterial dissemination worldwide. At the same time, the role of Asia in the recent SARS and bird flu outbreaks have made that continent a key area of interest. Emerging Infections in Asia offers a comprehensive overview of well studied and lesser-known infectious syndromes affecting local, regional, and international health, concentrating on their greatest areas of transmission. For each disease, contributors provide its historical record, biological structures, methods of transmission, clinical presentation, infection rates, methods of control and prevention, and potential threat to health on a global scale, in clear, accessible fashion. A sampling of the topics covered: Avian flu in Thailand. SARS outbreaks in China, Taiwan, and Singapore. HIV/AIDS in China. Human hemorrhagic fever in Saudi Arabia. Drug-resistant TB throughout Asia. E. coli in the developing world. By summarizing the knowledge base at this critical stage, Emerging Infections in Asia aids both epidemiologists and students of epidemiology in their efforts toward preparedness for and prevention of future pandemics. It is a bedrock volume in understanding this most pressing public health issue.